Conceptual Study of Balgrahas (Microbes) in Kaumarbhritya: A Narrative Review - Riya Rajendra Rathor; Renu Bharat Rathi; Shruti Prakash Kapatkar (Journal of Clinical and Diagnostic Research)
Ayurveda is a time-tested science that systematically explains its concepts through eight branches. Grahas Chikitsa (Ayurvedic treatment of microbes) is one of these branches, and it is well-explained in the texts. “Graha” refers to a tiny, invisible living organism that may undergo several stages of development and can be pathogenic or antigenic to the body. Microorganisms can cause generalised pathogenic alterations in the body that affect multiple systems, similar to the concept of Grahas. This suggests a deeper understanding of microbes in relation to Grahas. This review paper aims to explore the age-old concept of Balgrahas (microbes) and its relevance in modern times. The review was conducted using published articles on paediatric disorders, electronic databases, textbooks on paediatrics, and traditional Ayurvedic writings related to Kauamarbhritya (Paediatrics). A distinguishing feature of this study is its compilation of information on Balgraha from classical texts, covering clinical characteristics, causal factors, and various internal and external treatments. It also discusses Ayurvedic treatment modalities such as Daiva Vyapashraya Chikitsa (Spiritual therapy) and Yukti Vyapashraya Chikitsa (Rational therapy). In this review, authors discussed several formulations for treating conditions associated with Balgraha (microbes) that have not been detailed in previous studies. Additionally, some Shodhan karma (Detoxification) procedures that are particularly recommended for both children and nursing mothers are also highlighted.